Evidence that Argos is an antagonistic ligand of the EGF receptor. - Vinós, J; Freeman, M (2000)
Argos, the inhibitor of the Drosophila epidermal growth factor (EGF) receptor, remains the only known extracellular inhibitor of this family of receptors in any organism. The functional domain of Argos includes an atypical EGF domain and it is not clear whether it binds to the EGF receptor or if it acts via a distinct receptor to reduce Egfr activity indirectly. Here we present two lines of evidence that strongly suggest that Argos directly interacts with the EGF receptor. First, Argos is unable to inhibit a chimeric receptor that contains an extracellular domain from an unrelated RTK, indicating the need for the EGF receptor extracellular domain. Second, Argos can inhibit the Drosophila EGF receptor even when expressed in human cells, implying that no other Drosophila protein is necessary for inhibition. We also report that Argos and the Drosophila activating ligand, Spitz, can influence mammalian RTK activation, albeit in a cell-type specific manner. This includes the first evidence that Argos can inhibit signalling in mammalian cells, raising the possibility of engineering an effective human EGF receptor/ErbB antagonist. Oncogene (2000) 19, 3560 - 3562